Drug Repositioning with GraphSAGE and Clustering Constraints Based on Drug and Disease Networks - Zhang, Yuchen; Lei, Xiujuan; Pan, Yi; Wu, Fang-Xiang (Frontiers in Pharmacology, 2022)
The understanding of therapeutic properties is important in drug repositioning and drug discovery. However, chemical or clinical trials are expensive and inefficient to characterize the therapeutic properties of drugs. Recently, artificial intelligence (AI)-assisted algorithms have been received extensive attention for discovering the potential therapeutic properties of drugs and speeding up drug development. In this study, we propose a new method based on GraphSAGE and clustering constraints (DRGCC) to investigate the potential therapeutic properties of drugs for drug repositioning. First, the drug structure features and disease symptom features are extracted. Second, the drug-drug interaction network and disease similarity network are constructed according to the drug-gene and disease-gene relationships. Matrix factorization is adopted to extract the clustering features of networks. Then, all the features are fed to the GraphSAGE to predict the new associations between existing drugs and diseases. Benchmark comparisons on two different datasets show that our method has reliable predictive performance and outperforms several other six competing. We have also conducted case studies on existing drugs and diseases, and tried to predict drugs that may be effective for the novel coronavirus disease 2019 (COVID-19). Among the predicted anti-covid-19 drug candidates, some drugs are being clinically studied by pharmacologists, and their binding sites to COVID-19-related protein receptors have been found via the molecular docking technology.